2014
DOI: 10.1107/s2052520614000766
|View full text |Cite
|
Sign up to set email alerts
|

Strong positive and negative deviations from Vegard's rule: X-ray powder investigations of the three quasi-binary phase systems BiSX1 − xYx(X,Y= Cl, Br, I)

Abstract: Three quasi-binary phase systems, BiSX(1 - x)Y(x) (X, Y = Cl, Br, I; 0 < x < 1), have been investigated by X-ray powder diffraction. All three systems show unlimited solubility. For BiSCl(1 - x)Br(x) and BiSCl(1 - x)I(x), strong positive and negative deviations from Vegard's rule are observed with respect to the lattice parameters a and c. They are qualitatively explained by the asymmetry of the X coordination polyhedron and by anion-anion repulsions. For x < 0.32 [x > 0.32] the BiSCl(1 - x)I(x) system mimics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…These results clearly indicate the formation of BiSBr 1− x I x solid solution via anion substitution from BiOBr 1− x I x , with the retention of the original halogen contents. To the best of our knowledge, there is only one study 22 reported for the synthesis of a series of BiSBr 1− x I x solid solutions. However, the reported method requires multistep sealed-tube combustion, in which both high temperatures (~400 °C) and long reaction times (~1 week) are indispensable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results clearly indicate the formation of BiSBr 1− x I x solid solution via anion substitution from BiOBr 1− x I x , with the retention of the original halogen contents. To the best of our knowledge, there is only one study 22 reported for the synthesis of a series of BiSBr 1− x I x solid solutions. However, the reported method requires multistep sealed-tube combustion, in which both high temperatures (~400 °C) and long reaction times (~1 week) are indispensable.…”
Section: Resultsmentioning
confidence: 99%
“…Although rod-like BiSI particles can be produced at a low temperature of around 250 °C, by this method, the decreased iodine content was observed even at that temperature (e.g., ~0.8 of I/Bi at 250 °C, determined via EDX analysis); further decrease in the I/Bi value was observed at higher temperatures. Surprisingly, there is only one study 22 about the synthesis of bismuth chalcohalide BiSBr 1− x I x solid solution, in which BiSBr and BiSI particles were mixed and heated in a sealed tube under vacuum at a relatively higher temperature (~400 °C). However, this method involves multi-step reactions, including synthesis of the precursors (BiSBr and BiSI) and a long preparation time (~1 week).…”
mentioning
confidence: 99%
“…For example in BiSX 1−x Y x (X, Y = Cl, Br, I) the anisotropic unit cell variation is due to a rotation of the bismuth halide complex, which is consequent of the progressive elongation of the halogen−halogen interaction. 67 In the organic acridine/ phenazine system, the increased H•••H steric hindrance causes a similar molecular rotation that is responsible for the nonlinear relationship between volume and composition (Figure 3). 68 Structural changes can also occur in a discontinuous fashion.…”
Section: ■ Solid Solutions In Crystal Engineeringmentioning
confidence: 99%
“…An accurate structure analysis of these crystals can reveal the causes of such deviation and help in understanding the structure–composition relationship. For example in BiSX 1– x Y x (X, Y = Cl, Br, I) the anisotropic unit cell variation is due to a rotation of the bismuth halide complex, which is consequent of the progressive elongation of the halogen–halogen interaction . In the organic acridine/phenazine system, the increased H···H steric hindrance causes a similar molecular rotation that is responsible for the nonlinear relationship between volume and composition (Figure ).…”
Section: Solid Solutions In Crystal Engineeringmentioning
confidence: 99%
“…Given the challenges of making mixed-anion compositions, in most cases, reactants already featuring mixed-anion compositions, SbChX and BiChX (Ch = O, S, Se, Te; X = F, Cl, Br, I), were used as a starting material. These, in turn, were generally prepared by reacting Bi 2 Ch 3 and Sb 2 Ch 3 with BiX 3 and SbX 3 , respectively, or in the cases of BiTeI and SbTeI by reacting a stoichiometric mixture of elements. In one example, CsBr and BiSeBr were weighed in a nitrogen-filled glovebox in 1:1 molar ratio, targeting the 3D mixed-anion perovskite CsBiSeBr 2 . The mixture was carefully ground/homogenized inside the glovebox and then cold-pressed into a pellet.…”
Section: Computational and Experimental Methodsmentioning
confidence: 99%